Penggunaan Logo Zakat dalam Mengoptimumkan Kutipan Zakat Perniagaan Menurut Kerangka Maqasid Syariah di Malaysia - Afaf binti Sukari
Nowadays, the awareness of corporate companies in paying business zakat is still below the acceptable level. Zakat Collection Centre of Federal Territory Islamic Religious Council has stated that the accumulated amount of zakat that has been paid from corporate companies did not sum to the aimed target of RM1 billion. . While the level of awareness of business zakat payment among small traders in the state of Kedah is also at a moderate level (Sulaiman et al., 2019). In addition to that, it is also shown in the statistics that business zakat is surpassed by zakat al-mal which ranked first at largest sum of zakat collected. This is reprehensible, since if business zakat is optimized, it is guaranteed to possess a high potential to achieve the targeted sum of collected zakat. On that account, zakat institutions have been exerting efforts and works to optimise the zakat collection rate of corporate companies such as introducing wakalah programme, electing private agents, holding briefings to corporate companies’ personnel and so on. At present, a new approach by zakat institution has been initiated to encourage corporate companies to pay their zakat, which is by utilizing the zakat logo. The utilization of zakat logo is aimed to optimise the rate of collected zakat from corporate companies, consequently increasing the distribution of zakat itself especially towards asnaf group. Thus, this study is conducted to ascertain the utilization concept of zakat logo, in which is inaugurated by zakat institutions to corporate companies in Malaysia. This study also discusses the concept of Maqasid Syariah and its relations to the enactment of business zakat, as well as elaborating propositions for Maqasid Syariah framework, in utilizing zakat logo by zakat institutions to optimise the sum of business zakat in Malaysia. This study is conducted qualitatively by applying documentation and interview methods in the gathering of data. The result of this study has found that Kedah State Zakat Board (LZNK) is shown to be the first zakat institute that endorsed Zakat logo as a modern approach to optimise corporate zakat. The study also found that the zakat logo coincides with the framework of Maqasid Syariah in the context of Al-Dharuriyat, Al-Hajiyat and Al-Tahsiniyat in addition to giving good (maslahah) in general to zakat institutions, muzakki and asnaf towards achieving the overall objective of zakat shari'a. In addition, the result of this study, has proved that that the impact of utilization of zakat logo is not limited to increasing the rate of corporate zakat collection, but is also capable to become a marketing medium for a company, as well as building a corporate image and as a potential to give a substantial profit to the company. It is hoped that this study can be a reference, guideline, and foundation for zakat institutions to introduce the utilization of zakat logo that is conforming on Maqasid Syariah framework throughout the states in Malaysia as an initiative towards increasing the business zakat collection to the maximum sum from time to time.